2008
DOI: 10.1007/s11033-008-9282-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural appearance of linker histone H1/siRNA complexes

Abstract: Efficient non-viral vectors for the in vivo siRNA transfer are still being searched for. Comparing the differences of the structural appearance of siRNA and pDNA one would assume differences in the assembling behaviour between these polyanions when using polycationic vectors such as nuclear proteins. The spontaneous assembly of nuclear proteins such as histone H1 (H1) with pDNA as polyanion which has intensively been investigated over the last decade, showed a particulate structure of the resulting complexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our data on the oligonucleotides saturation with human H1(0) are closest to this value. Our system is similar to that described recently by Haberland et al43 where it was demonstrated that each H1 molecule can bind one or two ds21mers of siRNA that corresponds to from 42 to 84 bases/H1, also in agreement with our data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data on the oligonucleotides saturation with human H1(0) are closest to this value. Our system is similar to that described recently by Haberland et al43 where it was demonstrated that each H1 molecule can bind one or two ds21mers of siRNA that corresponds to from 42 to 84 bases/H1, also in agreement with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Somewhat paradoxically, after about four decades of extensive studies of linker histones–DNA interactions there is no generally accepted estimate of the stoichiometry for the binding of H1 to nucleic acids (see discussion in the paper of Mamoon et al19). Existing estimates vary in the rather wide range from 20 to 100 nucleotides per H1 molecule 17–19, 29, 41–43. Apparently, the most straightforward quantitative estimation of the stoichiometric number for H1–dsDNA binding was obtained in the work of Watanabe18 in the experiments on the DNA titration with the fluorescently labeled protein; but due to significant variation of the stoichiometric ratio estimates obtained in other studies the situation remains uncertain and accumulation of additional data obtained with different independent approaches is still required.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of the SSCrP nanocomplex was evaluated using the Gel-Red fluorescence quenching assay as described 10 . Briefly, twenty microliters of the SSCP nanocomplexes containing 1 μM siRNA with varying N/P rations were added to black 96 well plates along with 80 μL Gel Red solution.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of the SSCP nanocomplex was evaluated using the Gel-Red fluorescence quenching assay as described. 10 Briefly, twenty microliters of the SSCP nanocomplexes containing 1 μM siRNA with varying N/P ratios was added to black 96-well plates along with 80 μL of Gel Red solution. The plates were incubated at room temperature in the dark for 5 min, and fluorescence was measured using a Beckman DTX 880 multimode detector (Beckman Coulter, Inc., Brea, CA) at λ exc 485 nm and λ emi 625 nm.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%